Network Pharmacology and Molecular Docking Analysis of Nephelium lappaceum (Rambutan) Compounds as Potential Alternative Treatments for Lung Cancer - Utami, Dwi; Farid, Muhammad; Putri, Rachma Greta Perdana (Makara Journal of Science, 2025)
Introduction: Lung cancer is characterized by high mortality rates and poor prognosis, further requiring alternative therapies owing to the adverse effects of conventional chemotherapy. Rambutan (Nephelium lappaceum L.) has antimicrobial, antiproliferative, and antioxidant properties and can cure cancer. Method: Compounds from rambutan peel were identified through PubChem and analyzed for physicochemical properties using SwissADME. Target proteins were identified using SuperPred and compared with lung cancer–related proteins from GeneCards via Venny. Protein interactions were examined and visualized using STRING and Cytoscape, respectively. Protein activity was analyzed using WebGestalt, and docking simulations were performed using Autodock 4.2.6. Result: Physicochemical analysis of 10 active rambutan compounds via SwissADME showed favorable properties based on Lipinski’s rule, suggesting good oral bioavailability. In total, 276 specific target proteins were related to lung cancer. Cytoscape visualized the 53 core proteins implicated in lung cancer. Gene ontology and Kyoto Encyclopedia of Genes and Genomes analyses indicated that rambutan compounds are active in lung cancer pathways, particularly nonsmall cell lung cancer. The analysis identified the top 10 interacting proteins STAT3 and CASP3 had the highest interaction value of 28, followed by PIK3CA and NFKB1 at 22, MAPK3, PIK3R1, PTGS2, GRB2, MAPK1, and CASP8. Per docking simulations, 1,2-diphenylethane-1-ol was the highest affinity to STAT3 (−4.78) and CASP3 (−6.75). Conclusion: Rambutan peel compounds have remarkable anticancer potential, particularly with high affinity for STAT3 and CASP3 proteins, based on in silico molecular docking studies.